Likwidacja Zbiornicy Księgozbiorów Zabezpieczonych w Poznaniu - Nowicki, Ryszard (Biblioteka Uniwersytecka w Poznaniu, 2014)
Po II wojnie światowej, 1 lutego 1947 roku, w Polsce powstało siedem zbiornic-segregatorni. Jedną z nich była Zbiornica Księgozbiorów Zabezpieczonych w Poznaniu. Zgromadziła ona liczne zbiory zwłaszcza z terenów Wielkopolski, Dolnego Śląska oraz Pomorza Zachodniego. Woluminy przekazywane były, za zgodą władz państwowych, przede wszystkim instytucjom naukowym. Formalna likwidacja Zbiornicy nastąpiła 31 grudnia 1949 roku. Jej zasoby, liczące około 286 000 tomów, przejęła Biblioteka Uniwersytecka w Poznaniu, która kontynuowała prace związane z segregacją, repartycją oraz zwożeniem książek z terenu. W 1953 roku w magazynach byłej poznańskiej Zbiornicy pozostawało ponad 250 000 tomów, głównie poniemieckiej proweniencji. Dzieła te zostały przekazane Zbiornicy Księgozbiorów Zabezpieczonych w Katowicach oraz Bibliotece Uniwersyteckiej w Poznaniu. Część książek, uznanych za zbędne, przeznaczono na makulaturę.

Soon after WWII, seven storehouses and sorting houses were established in Poland (on February 1st, 1947). One of them was the Storehouse of Secured Libraries in Poznań. The storehouse was used to house numerous “abandoned” book collections, in particular those from the Wielkopolska region, Lower Silesia and Western Pomerania. Following formal approval of the authorities, volumes of books were then transferred to various research and scientific institutions. Formally, the Storehouse was liquidated on December 31st, 1949. Its resources, amounting to about 286,000 volumes were taken over by Poznań University Library. The library carried on with the relevant work on segregation, processing, restoration and recovery of books form the designated areas. In 1953, the storehouse still kept more than 250,000 volumes, mainly from former German libraries and book collections. These books were then transferred to the Storehouse of Secured Libraries in Katowice and to Poznań University Library. A number of books deemed to be redundant for the purposes of the libraries involved were subsequently pulped, discarded, or otherwise abused.
Removal and clearance of the Storehouse of Secured Libraries in Poznań
Keywords: Poznań; libraries; biblioteki; preservation of collections; ochrona zbiorów; 19th century; XX wiek